2000
DOI: 10.1042/bst0280027
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modulation of chemotherapy resistance in cultured oesophageal carcinoma cells

Abstract: Oesophageal carcinoma is a common form of cancer in developing countries, especially in the Caspian littoral and northern China. In contrast, it has a much lower incidence in Japan, the U.S.A. and western Europe. Certainly in the case of squamous cell oesophageal carcinoma, dietary composition, smoking, alcohol and exposure to nitrosamines are major risk factors that may partly explain the disease's geographical distribution. The prognosis for oesophageal carcinoma is generally poor, due to the high incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The IC 50 of cisplatin, measured via the MTT assay, was 18.5 ± 6.4 µM whilst that of 5-fluorouracil was 14.1 ± 3.8 µM. Both IC 50 values were measured in WHCO1 cells over 24 h. The IC 50 was determined as the concentration of drug needed to kill 50% of cells over 24 h. Similar IC 50 values have been obtained before [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Our preliminary experiments showed that the use of concentrations above 10 µM would result in considerable cell death, and we used concentrations less than half the IC 50 value ( Supplementary Figure S1A–C ).…”
Section: Resultssupporting
confidence: 67%
“…The IC 50 of cisplatin, measured via the MTT assay, was 18.5 ± 6.4 µM whilst that of 5-fluorouracil was 14.1 ± 3.8 µM. Both IC 50 values were measured in WHCO1 cells over 24 h. The IC 50 was determined as the concentration of drug needed to kill 50% of cells over 24 h. Similar IC 50 values have been obtained before [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Our preliminary experiments showed that the use of concentrations above 10 µM would result in considerable cell death, and we used concentrations less than half the IC 50 value ( Supplementary Figure S1A–C ).…”
Section: Resultssupporting
confidence: 67%
“…91 BSO was used to modulate the levels of GSH within two squamous oesophageal carcinoma cell lines that were resistant to alkylating agents (cisplatin), but not Vinca alkaloids and doxorubicin. 92 BSO has also been used to sensitize previously resistant human ovarian cancer cells to cyanomorpholino doxorubicin (MRA-CN) by altering GSH levels, 93 and in a neuroblastoma cell line, enhanced cytotoxicity was observed when treated with a combination of both melphalan and BSO compared to melphalan alone. 94 Pan et al used a slightly different approach, and were able to reverse the resistance of a human ovarian cancer cell line to cisplatin by treatment with a c-jun antisense oligodeoxynucleotide, which decreased the level of cellular GSH.…”
Section: Glutathione and Anti-cancer Therapymentioning
confidence: 98%
“…Ethacrynic acid (EA) is a clinically used high‐ceiling loop diuretic, often used to treat high blood pressure or edema, such as in cases of infant congestive heart failure (Kay et al, 2001). Although it is being phased out of use as a diuretic, it is currently being looked at as a chemotherapy enhancing agent due to its known inhibitory activity on the glutathione‐S‐transferase (GST) family of enzymes (Tew et al, 1998; Sheehan and Meade, 2000; Gate and Tew, 2001). EA is an α,β‐unsaturated ketone which is able to react with glutathione (GSH) spontaneously leading to its known GSH depletory effects in both cytosol and mitochondria (Seyfried et al, 1999).…”
mentioning
confidence: 99%